Consolidation therapies revisited: weekly paclitaxel. (1st October 2003) - Pecorelli, S.; Odicino, F.; Favalli, G.
Abstract : Most patients with advanced ovarian cancer exhibit clinically relevant objective and subjective responses to platinum/paclitaxel-based combination, which is now considered the standard chemotherapeutic regimen. Unfortunately, responses are generally of limited duration, and long-term disease-free survival is experienced by few patients. Efforts should be taken to maintain such a response as long as possible, where it realistically might be hoped that continuation of chemotherapy could consolidate the absence of clinically detectable disease. In this regard, the administration of paclitaxel on a weekly schedule seems to be particularly attractive, especially after the demonstration that a weekly regimen in heavily pretreated women bearing metastatic breast, head, and neck or lung cancers was proven to be well tolerated without the requirement of granulocyte colony-stimulating factors, with limited neurotoxicity and with substantial anticancer activity, thanks to its pro-apoptotic and antiangiogenesis properties. In Italy, a multi-institutional phase II prospective study (After-6 Protocol 2) has been initiated to verify the effectiveness of paclitaxel, administered on a weekly schedule (60 mg/m 2 for 21 courses), in patients bearing microscopic residual disease detected at second-look operation to define its effectiveness after completing their primary platinum/paclitaxel chemotherapy treatment. When possible, patients were surgically re-evaluated thorough a third-look operation to evaluate the percentage of conversion of microPR into a pathological complete remission status. An interim evaluation based on 534 cycles administered to 41 patients showed than only one patient experienced grade 4 anemia, 7.4% grade 2 transient peripheral neurotoxicity, and 2.7% delay in treatment delivery. Therefore, weekly paclitaxel has been proven to be easily administered even in heavily pretreated patients, with acceptable hematological and neurological toxicity.